Study of structure stability in a mathematical model of four interacting groups - Anna Stanislavovna Adamchuk; Stanislav Raufovich Amirokov; Tatyana Konstantinovna Pritula (Наука. Инновации. Технологии)
We will discuss the problem of mathematical modeling of dynamic processes and structure change in a model with four interacting groups using a system of Walter's nonlinear differential equations. We will show that it is possible to find a stationary state with positive coordinates when all groups exist. We will also suggest an algorithm and a program for finding the stationary state with non-zero coordinates and testing its stability in a mathematical model of dynamics between four interacting groups.